74–14 SAAL and the Architecture#: International Colloquium - Bandeirinha, José (Docomomo Journal, 2022)
SAAL (Serviço de Apoio Ambulatório Local), Local Ambulatory Support Service, was a program for the construction of houses in poor neighborhoods. It followed the revolu- tionary process which, in 1974, brought to an end half a century of dictatorship in Portugal. Although properly contextualized in a very specific historical process, nowadays it is still a tool to think, to question and to debate the issues and challenges of housing as well as its ineludible proximity to architecture.